The Use of Podcast in Teaching Listening Comprehension - Wardah Arum Anandari; Ida Isnawati (Universitas Nias, 2023)
As todays’ generation belongs to Z generation who has been familiar with technology and internet from their young age, it is expected that teachers can maximize their function as learning facilitators by making use of technology and internet resources as learning media. Podcast is one of technology learning media that can be used in teaching listening. For this reason, the present study was intended to examine the effects of using podcast as the media for teaching listening comprehension in students’ listening ability. Two intact classes of 60 eight graders taking an English class at one secondary school in Tulungagung, East Java were involved in this study. A listening test in multiple choice format was developed for use as the instrument to collect data. The findings show that there is a statistically significant difference in the mean scores of the students’ listening ability when they were taught by using podcast and those taught without using podcast. Thus, it could be concluded that the use of podcast media is effective for teaching listening comprehension in the eighth grade of secondary school.